Comparison of the Level of Smoking Dependence on Psychological Aspects Among Technical Students - Asraf Johar Salleh; Ahmad Jazimin Jusoh; Amelia Mohd Noor (International Journal of Education, Information Technology, and Others, 2022)
This study compared the psychological effects of low, medium and high smoking dependence among technical students. The psychological aspects tested were irrational beliefs, stress and willingness to quit smoking. This survey study involved 100 participants aged 18 to 25 from technical institutions in Perak, Malaysia. The Glover-Nilson Smoking Behavior Questionnaire (GN-SBQ) was used to assess smoking dependence. The Smoking Rationalization Scale (SRS) was used to assess smokers' irrational beliefs, the Perceived Stress Scale (PSS) was used to assess stress, and the University of Rhode Island Change Assessment Scale (URICA) was used to assess willingness to quit smoking. Using the Statistical Package for the Social Sciences (SPSS), data were analyzed using cross-tabulation and MANOVA to determine descriptive and inferential findings. The study's findings show a significant difference between low, moderate and high levels of smoking dependence in terms of irrational beliefs, stress, and willingness to quit smoking. The study's results also show that high and moderate smoking dependence smokers have a relationship with high levels of irrational beliefs, high stress and low willingness to quit smoking. These findings suggest smokers should be exposed to intervention and treatment programs to reduce smoking habits among technical students.